Endoscopic ultrasound‐guided ablation of branch‐duct intraductal papillary mucinous neoplasms: Feasibility and safety tests using porcine gallbladders. Issue 5 (30th March 2016) - Park, Jin‐Seok; Seo, Dong‐Wan; Song, Tae Jun; Park, Do Hyun; Lee, Sang Soo; Lee, Sung Koo; Kim, Myung‐Hwan
Abstract : Background and Aim: Radiofrequency ablation (RFA) and ethanol ablation are accepted methods of tissue destruction for treating cystic tumors. The aim of the present study was to evaluate the feasibility, efficacy, and safety of endoscopic ultrasound (EUS)‐guided ablation using normal porcine gallbladders as a substitute model for branch‐duct intraductal papillary mucinous neoplasms (BD‐IPMN). Methods: Six adult mini pigs were included in this prospective study. EUS‐guided RFA with or without ethanol ablation of the gallbladder was carried out using a prototype 18‐gauge endoscopic RFA electrode, and RFA and ethanol ablation were done in a single session. Outcomes were assessed in terms of macroscopic and microscopic evaluations of the treated gallbladders. Results: The prototype RFA electrode was used for ablation of the mucosa, aspiration of the internal contents of the gallbladder, and ethanol injection. RFA plus ethanol lavage resulted in a greater mean percentage of denuded gallbladder mucosa (97.5%) than RFA alone (55.8%). Effects of ablation extending to the cystic duct and partially denuded cystic duct mucosae were detected in five of the six pigs. There were no major procedure‐related adverse events. Conclusions: EUS‐guided ablation of the gallbladder mucosa was feasible and effective in the porcine model. Additional studies will be required to fully assess the risk of procedure‐related damage to the main pancreatic duct before using this technique in a clinical setting.